A review of wind turbine noise measurements and regulations. Issue 4 (August 2016) - Raman, Ganesh; Ramachandran, Rakesh C; Aldeman, Matthew R
Related reviews are given of (1) international wind turbine noise regulations and standards and (2) modern experimental methods in aeroacoustic measurement with sample applications. For the latter, specific emphasis has been placed on three measurement techniques: (1) single microphone measurements, (2) phased microphone array measurements, and (3) compact microphone array measurements. Through a description and analysis of recent successful application scenarios of the above techniques, their immense potential utilizing experimental aeroacoustics is explained.